Scrotal Pearls and Hydrocele: A Unique Case of Scrotal Lithiasis - Korrapati, Bhavyadeep; Mani, Vijayanand; Palaniyandi, Velmurugan; Sekar, Hariharasudhan; Krishnamoorthy, Sriram (Curēus (Palo Alto, CA), 2025)
Scrotal calculi are uncommon, benign stones that typically form within the hydrocele sac, often due to chronic inflammation, minor trauma, or torsion of the appendix testis, and are incidentally detected during imaging or surgery. Although rare, scrotal calculi have been reported to occur in specific groups, such as athletes, who experience repetitive mechanical stress. A 56-year-old diabetic male presented with a two-year history of painless scrotal swelling. The swelling is not associated with any trauma. On physical examination, the swelling transilluminated, and an ultrasound revealed an 8-cm hydrocele with a 1.4-cm free-floating lesion, which was isoechoic to the surrounding tissue. The testes and epididymis appeared normal. Surgical exploration confirmed the presence of the hydrocele and a 1.4-cm, pearly white, free-floating scrotal calculus, which was removed. The tunica vaginalis was excised, everted, and plicated to prevent future recurrence of the hydrocele. While rare, scrotal calculi should be considered when a free-floating lesion is detected in the scrotal sac, especially in association with a hydrocele. Surgery is the treatment of choice if patients are symptomatic and generally have a favorable prognosis. Further studies are needed to clarify the underlying causes of scrotal calculi and their prevalence, particularly in populations subject to repetitive scrotal trauma, such as athletes.